Conflicts and cooperation in the opening-up of new economic resources: The Third UN Conference on the Law of the Sea - Klaus Dieter Wolf (Intereconomics, 1980)
The Third United Nations Conference on the Law of the Sea (UNCLOS III) will meet in March for its ninth session. The size of the resources available for distribution and their allocation by the Conference are surveyed in the following article as are the possibilities of conflict to which they give rise.
Keywords: 330; Law of the Sea